Optimization and control of polystyrene batch reactor using hybrid based model - Hosen, M.A.; Hussain, Mohd Azlan (Computer Aided Chemical Engineering, 2012)
The effects of operating conditions such as initiator and monomer concentration as well as reactor temperature of polymerization reactors have been studied in this work. A recently developed hybrid model for polystyrene batch reactor was utilized in simulation study. The simulation results revealed the sensitivity of polymer properties and conversion to variation of these operating conditions. Furthermore, the study deals with the optimization of batch polymerization reactors. The optimization problem involving minimum time optimal temperature policy has been formulated and solved. Different numerical techniques have been tested and compared. The online control works were performed to validate the optimal temperature profiles. The experimental studies reveal that the calculated optimal policies were able to reduce the batch time keeping the same polymer quality. Â© 2012 Elsevier B.V.